PERLINDUNGAN KONSUMEN TERHADAP PENGGUNAAN KOSMETIK YANG TIDAK TERDAFTAR PADA BPOM - Triyana Syahfitri (Fakultas Hukum Universitas Islam Indragiri, 2018)
Consumer Protection Act Article 4 letter a which states that consumers have the right to comfort, security and safety in consuming goods and / services, so that goods circulated in the market must go through an Official Independent Institution formed by the Government which functions to oversee the circulation of each drug product, food and beverages circulating in Indonesia, namely the Food and Drug Supervisory Agency (BPOM). The BPOM Code is given as a guarantee that the goods consumed are healthy or harmless if consumed. Products that have been coded BPOM means that consumers use products that have safe quality and do not endanger health. But in reality there are still many markets on the product that are without the BPOM code, for example products in the form of female cosmetics.